2017
DOI: 10.1080/14767058.2017.1355907
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of oxytocin versus carbetocin in prevention of postpartum hemorrhage after cesarean section under general anesthesia: a prospective randomized clinical trial

Abstract: It may be concluded that carbetocin is a good alternative modality to conventional uterotonic agents such as oxytocin for the prevention of postpartum hemorrhage after cesarean sections. Registration ID in IRCT: NCT02079558.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 23 publications
1
23
0
Order By: Relevance
“…1). After exclusions, five RCTs were included in the review, [22][23][24][25][26] with a total of 1,214 patients. Table 1 outlines the study characteristics.…”
Section: Resultsmentioning
confidence: 99%
“…1). After exclusions, five RCTs were included in the review, [22][23][24][25][26] with a total of 1,214 patients. Table 1 outlines the study characteristics.…”
Section: Resultsmentioning
confidence: 99%
“…We used the dosing scheme (and the PPH risk) described by Borruto et al 22 and Attilakos et al 23 because they included women with at least one risk factor for PPH. In other studies, using even higher doses of oxytocin, [26][27][28][29] the risk reduction with carbetocin was even greater; however, there are differences in the characteristics of the population, particularly related to the level of risk that does not allow to clearly observe the differences between alternatives, so it was preferred to adopt a conservative scenario. Regarding utility values, these were based on international studies, since there are no quality of life studies available in our country, and these may not necessarily reflect the preferences of Colombian patients.…”
Section: Discussionmentioning
confidence: 98%
“…24 According to the results of a randomized clinical study, it was concluded that carbetocin may be a good alternative modality to traditional uterotonic agents such as oxytocin to prevent PPH in patients with cesarean operation under general anesthesia. 25 Meanwhile, although we used 100 μg of carbetocin which was the recommended dose in our study, in a randomized controlled study, patients were given 20, 40, 60, 80 or 100 μg doses and PPH amounts were compared. The results of the study showed that 20-100 μg carbetocin doses were similarly effective in women with low PPH risk undergoing elective cesarean delivery.…”
Section: Discussionmentioning
confidence: 99%